#TITLE_ALTERNATIVE# - ESTI RAHMAYANTI (NIM: 25312308), ADE
Limitation of freshwater resources in coastal areas is the background of the utilization of any water resource available to meet the daily water use of coastal communities by getting better quality water source away from their homes at a great price. Clean water crisis in terms of quality, quantity, continuity, and the difficulty of gaining access to clean water for daily use, especially for the use of drinking water make this issue as one of the most prominent problems in almost all coastal areas. Rainwater is one of free water sources available that has not been used optimally for various domestic purposes, including drinking water. Roof of the house is the main component in a rainwater harvesting system thus beside of the condition of the environment, roof of the house could also give significance impact towards the quality of the harvested rainwater. This study aims to determine the ideal time for harvesting rainwater done within two different time: PAH1 (sample taken on February 19th 2015 whereas no rain prior) and PAH2(sample taken on February 24th 2015 whereas rain occurred four days in row prior), the ideal location for harvesting rain (industrial and non industrial areas), and ideal roofing material for harvesting rain (asbestos, metal sheet and clay tiles) and also the reliability level of the rainwater at the area of the study as an alternative of daily needs water source. Some water quality parameters (pH, turbidity, temperature, TDS, Fluoride, Nitrite, Nitrate, Iron, Zinc, Cadmium, Chromium) were analyzed and the results were compared to drinking water standard based on the Regulation of the Minister of Health No. 492 of 2010. There are seven parameters of water quality which exceeded the standard of sixteen water quality parameters analyzed. The type of the roof influenced the quality of the harvested rainwater whereas PAH1 is better than PAH2. The quality of the rain water in the industrial area is worse compared to the non industrial area due to the industrial activities. Clay tile roof is the most ideal roofing material for harvesting rainwater with one heavy metal concentration exceeded the standard, there are Lead reaching 2,0916 mg/L. Meanwhile metal sheet is considered as the worse with four type of heavy metal exceeded the standard, there are iron (0,5506 mg/L): Cadmium (0.0204 mg/L); Manganese (10,6256 mg/L); and Zinc (4,7669 mg/L). (Cd) concentration contained in harvested rainwater after several rain events (0.0204 mg/L) is higher than the first rains (0.0123 mg/L). The quantity of rainwater as a supporting capacity in drinking water through rainwater harvesting is indicated by the level of reliability (Re) through simulated rainwater tank capacity of 1 m3 and 1,5 m3 using daily rainfall data for three consecutive years and simulations showed that the reliability of rainwater as an alternative source of drinking water attained 88,50% and 53,47% for the tank capacity of 1 m3 and the rainwater reliability level as an alternative for drinking water based on the survey was 95,53%. While for the tank capacity of 1,5 m3 the rainwater reliability level as an alternative for drinking water and cooking purpose were 92,43%; 60,68% and 97,26%. Socio-economic survey shows that not many local people are aware of the benefits of utilizing rainwater and some of them even have a misunderstanding regarding the quality of rainwater. Negative perceptions about rainwater harvesting is that rainwater harvesting is not a common thing to do, especially in areas close to urban.